UTILIZATION OF IMAGE AND SIGNAL PROCESSING TECHNIQUES FOR ASSESSMENT OF BUILT HERITAGE CONDITION - Petr Koudelka; Veronika Koudelková; Tomáš Doktor; Ivana Kumpová; Daniel Kytýř; Jaroslav Valach (Acta Polytechnica CTU Proceedings, 2018)
Historical buildings represent invaluable heritage from the past and therefore their protection is a very important task. Assessment of their condition must not cause damage accumulation, thus the least possible volume removed from the structure is essential. As many historical buildings in the Czech Republic are built using sandstone that can be considered as a typical heterogeneous system, statistical signal processing is a promising approach for determination of the representative volume element (RVE) dimensions. Such calculations can be carried out on the domain of logical arrays representing binary images of the materials microstructure. This paper deals with processing of image data obtained using SEM-BSE and high resolution flatbed scanner for determination of RVE dimensions. Advanced image processing techniques are employed and results from calculation using grayscale data are presented and compared with results calculated on the basis of color input images.